2000
DOI: 10.1080/10587250008023531
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Dependence of the Magnetization of MII (N(CN)2)2: Mechanism for the Long Range Magnetic Ordering

Abstract: The ac-susceptibilities of the isostructural metal-organic magnets, M"(N(CN)&(M = Ni (l), Co (2) and Fe (3)) have been studied as a function of temperature and pressure. Large variation in behaviors has been observed: the transition temperature initially increases in all three compounds and at higher pressures that for (1) saturates, for (2) decreases and for (3) increases continuously. These behaviors are due to the competition between antiferromagnetic (tZg tf cg) and ferromagnetic (tZg tf t2g and e tf eg) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
32
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 13 publications
5
32
0
Order By: Relevance
“…37 The pressure-dependent magnetic behaviour can become more complex in systems for which the magnetic exchange arises from a contribution of both FM and AFM interactions. 29,38 In these cases, FM compounds have a greater tendency for their T C to remain unchanged or decrease with pressure, while the AFM compounds generally exhibit an increase of T N with pressure. 12,35,38 This observation can be understood by the response of AFM interactions to both M-L-M binding angle and the M-L bond distances, whilst FM interactions are most sensitive to the M-L-M binding angle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The pressure-dependent magnetic behaviour can become more complex in systems for which the magnetic exchange arises from a contribution of both FM and AFM interactions. 29,38 In these cases, FM compounds have a greater tendency for their T C to remain unchanged or decrease with pressure, while the AFM compounds generally exhibit an increase of T N with pressure. 12,35,38 This observation can be understood by the response of AFM interactions to both M-L-M binding angle and the M-L bond distances, whilst FM interactions are most sensitive to the M-L-M binding angle.…”
Section: Introductionmentioning
confidence: 99%
“…29,38 In these cases, FM compounds have a greater tendency for their T C to remain unchanged or decrease with pressure, while the AFM compounds generally exhibit an increase of T N with pressure. 12,35,38 This observation can be understood by the response of AFM interactions to both M-L-M binding angle and the M-L bond distances, whilst FM interactions are most sensitive to the M-L-M binding angle. 35 Ammonium metal formates, as well as related metal formates ([A][M(HCOO) 3 ]) with protonated amine-templating cations on the A-site, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Fe(N(CN) 2 ) 2 and Ni(N(CN) 2 ) 2 compounds show an increase of the transition temperature of 26% and 6%, respectively, for pressures as large as 17 kbar, whereas the Co(N(CN) 2 ) 2 undergoes a transition from ferromagnetic to antiferromagnetic interactions at nominally 13 kbar. 11 Herein, low and high field dc and ac magnetization studies for Mn(N(CN) 2 ) 2 are reported as a function of pressure up to 12.1 kbar. The data indicate an increase in the strength of the superexchange interaction with pressure and the appearance of a large magnetic anisotropy above 8.6 kbar.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32][33] Mn[N(CN) 2 ] 2 is a particularly important member of this series. [34][35][36][37][38] In the Pnnm structure, the Mn(II) centers are connected by soft N≡C-N ligands that act as magnetic superexchange pathways.…”
Section: Introductionmentioning
confidence: 99%